Configuration Laptop Usage During Online Class: Effects on Posture and Discomfort Using the REBA Method - Dian Palupi Restuputri; Rozza Badiiliana I; Fatimah Zahra Y; Nanindya Aisyah P; Fita Amalia; Yuniar Rizky K; Nella Ayu Y (Universitas Muhammadiyah Malang, 2021)
COVID-19 has become a global pandemic, and one of the government's actions in the education sector to prevent transmission through online class activities or online classrooms has been adopted. During the pandemic, it was discovered that using computers with improper or non-ergonomic body postures during online classes might cause muscular fatigue and raise the incidence of musculoskeletal problems. Using the Rapid Entire Body Assessment (REBA) method, this study seeks to detect musculoskeletal complaints and assess the posture of UMM students when using a laptop. Because online learning lasts more than 2 hours, posture that is not in accordance with the comfort of using a laptop can lead a person to exhaust more rapidly in front of a laptop for a relatively long period, especially in the upper neck, back, and waist, which stand for 80% of the body parts. This is supported by the study of respondents using a questionnaire distribution technique that provided a REBA score of 7 and a moderate risk level, indicating that remedial action is required. After a recommended improvement with a low risk level for MSDs, a REBA score of 3 was established. Suggestions that can be considered are that it is necessary to improve sitting work posture, it is recommended to work on a table and sit in a reclining chair so that the proposed work posture improvement can be carried out.